Beyond productivity and efficiency: design tools, methods and frameworks for psychological well-being, and (un)exploited potentials to assist employees at work - Dhiman, Hitesh; Nemoto, Yutaro; Fellmann, Michael; Röcker, Carsten (Frontiers in Computer Science, 2023)
Research has repeatedly demonstrated that fostering employees' psychological well-being is linked to several positive outcomes, both for the employee and the organization, and yet, it has rarely been considered as a design goal, especially when it comes to developing digital solutions to assist employees in their everyday tasks. In this paper, we take the first steps toward using well-being concepts to (re)design assistants. We motivate the problem by providing an overview of assistance technologies in the industrial context and their current state of development. Next, we elucidate and map the facets of psychological well-being at work, and highlight the importance of workplace eudaimonic well-being. To help designers and researchers adopt it as a design objective, we carried out a literature review to synthesize the state-of-the-art frameworks and methods that have been proposed to incorporate psychological well-being into design. Our investigation reveals that no one framework targets eudaimonic well-being, and more work may be necessary to develop a comprehensive approach that targets the various facets of workplace eudaimonic well-being. Consequently, we discuss challenges and opportunities for developing digital assistance that could foster employees' psychological well-being.